International law and governance of natural resources in conflict and post-conflict situations - Dam-de Jong, Daniëlla (Cambridge studies in international and comparative law ;, 2015)
"Natural resource wealth is conducive to a country's development. Nevertheless, the last few decades have shown a harsher reality, where natural resources have also triggered, financed or fuelled a number of internal armed conflicts. Examples include the armed conflicts in Cambodia, Sierra Leone, Liberia and the Democratic Republic of the Congo, which have been financed with the exploitation of a variety of valuable natural resources, including diamonds, gold, timber, oil and cocoa. The aim of this book is to assess the contribution of international law in ensuring that natural resources are used to promote development and to achieve sustainable peace instead of financing armed conflict. For this purpose, the author discusses the international legal framework for the governance of natural resources in States in general, in situations of armed conflict and as part of conflict resolution and post-conflict peacebuilding efforts"--